The Impact of the Capital Adequacy Ratio, Non-Performing Loan Against to Return on Equity (Case Study Private Bank in Indonesia) - Sebayang Pirmanta (SHS Web of Conferences, 2020)
Banks in Indonesia always pay attention to the Capital Adequacy Ratio (CAR) to obtain adequate bank performance, while also paying attention to Non-Performing Loan (NPL). Banks want a high Return on Equity (ROE) to be able to be declared healthy and the bank's performance is also very good. Banking companies always make financial reports related to the banking performance. This study has two objectives namely, first to examine the effect of Capital Adequacy Ratio (CAR) on Return on Equity (ROE). Second, to examine the effect of Non-Performing Loans (NPLs) on Return on Equity (ROE) in foreign private banks that have been determined by the government. This study uses multiple regression analysis techniques using a sample of 20 banks. The test results show that there is an increase in capital Adequacy Ratio (CAR) that will be able to increase the Return on Equity (ROE) of foreign private banks in Indonesia. Increased Non-Performing Loans (NPLs) can have a positive effect and increase Return on Equity (ROE). Simultaneous tests carried out obtained the variable Adequacy Ratio (CAR) and Return on Equity (ROE) to have a joint impact on the Return on Equity (ROE) of private banks.